The impact of COVID-19 on infection control practices in dentistry: adaptations and challenges: a literature review - Ahmed, Murtada A.; Alshayeb, Fares R.; Alshahry, Layla H.; Alshakhs, Sarah A.; Alshahrani, Nahla H.; Almutairi, Amal Z.; Alwethainani, Ohoud M.; Almomtin, Zainab H.; Alanazi, Norah H.; Alotaibi, Suha D.; Alsaleem, Afnan I. (International Journal Of Community Medicine And Public Health, 2024)
COVID-19, which emerged in late 2019, has significantly affected global health and daily life, particularly in clinical settings due to its high transmissibility. This necessitated rapid adaptations in infection control measures to protect patients and healthcare providers. This literature review synthesizes studies on the impact of COVID-19 on dental infection control, highlighting the adaptations and challenges faced by practitioners during this period. A comprehensive search strategy was employed, utilizing databases such as PubMed, Scopus, and Web of Science to identify relevant studies published from 2020 to 2024. Inclusion criteria encompassed articles discussing infection control protocols and adaptations in practice. Studies show a shift to stricter personal protective equipment (PPE) use, including N95 respirators and face shields, despite shortages and limited training. High-risk aerosol-generating procedures (AGPs) led to research on reducing aerosol production through high-volume suction and rubber dams. Patient screening and triage became essential, while telehealth facilitated remote consultations. Environmental controls emphasized better ventilation, air filtration, and effective disinfectants like high efficiency particulate air (HEPA) purifiers. Overall, dental practices adapted to COVID-19, accelerating teledentistry to enhance accessibility and reduce infection risks. The COVID-19 pandemic necessitated major changes in dental infection control practices, enhancing PPE use, aerosol management, patient screening, and environmental controls, despite challenges. Teledentistry emerged as valuable for remote care but faces integration barriers. Future research should address these challenges, establish standardized protocols, and assess the long-term effects on infection control.